Does Aerobic Vaginitis Have Adverse Pregnancy Outcomes? Prospective Observational Study. (18th January 2020) - Hassan, Mahmoud F.; Rund, Nancy M. A.; El-Tohamy, Osama; Moussa, Mahmoud; Ali, Yahia Z.; Moussa, Nehal; Abdelrazik, Ahmed A.; Abdallah, Enas A. A.
Abstract : Background . Aerobic vaginitis (AV) is an aberration within the balanced vaginal microbiota. Only few reports have documented the adverse pregnancy outcomes related to AV. Nonetheless, the exact role of AV in pregnancy and the potential benefit of its screening need further study. Our goal was to evaluate the association between aerobic vaginitis (AV) in late pregnancy and maternal and neonatal outcomes. Methods . In this prospective observational study, a total of 600 singleton pregnant women with intact fetal membranes at a gestational age of 34-36 weeks were recruited (one hundred women with AV and 500 pregnant women without AV). The study protocol excluded patients with other forms of vaginal infection. Pregnancy outcomes were traced and documented. The primary outcome was the association between AV and preterm labor. The current study compared the maternal and neonatal outcomes among pregnant women with and without AV in unadjusted and adjusted analyses with the odds ratio (OR) and 95% confidence interval (CI) reported. Results . There was an association between AV and with preterm birth (adjusted OR 3.06, 95% CI 1.58-5.95) and prelabor rupture of membranes (adjusted OR 6.17, 95% CI 3.24-11.7). For neonatal outcomes, AV was associated with a higher incidence of neonatal ICU admission (adjusted OR 2.19, 95% CI 1.1-4.34). Severe forms of AV significantly increased the incidence of PTB (p = 0.0014 ) and PROM (p = 0.0094 ) when compared to less severe forms of AV. Conclusion . AV is common in late pregnancy and is linked to a diversity of adversative pregnancy outcomes including preterm birth, PROM, and neonatal ICU admission. Moreover, the incidence of PTB and PROM might further increase with the severity of AV. Clinicians should pay more consideration to vaginal microbiota assessment during pregnancy.